Aktivitas Penghambatan enzim Dipeptidyl Peptidase 4 (DPP-4) dari ekstrak dan seskuiterpen lakton yang Diisolasi dari Daun Yacon (Smallanthus sonchifolius) - Tamhid, Hady Anshory; Hertiani, Triana; Murti, Yosi Bayu; Murwanti, Retno (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
The Sesquiterpene lactones, enhydrin and uvedalin, are the chemotype and subtype compounds of the yacon leaf. They are known to have anti-diabetic activity, but their mechanisms are not clear. One of the mechanisms of anti-diabetic agents is to inhibit the activity of the dipeptidyl peptidase 4 enzyme (DPP-4). The research aimed to determine the inhibition of the extract, enhydrin, and uvedalin isolated from the yacon leaf against the DPP-4 enzyme activity. Yakon leaves were extracted using 70% ethanol by the maceration method. Enhydrin and uvedalin were obtained from previous research. The inhibitory activity of the DPP-4 enzyme was then determined by the fluorescence assay method using a multi-well plate reader. Sitagliptin was used as standard inhibitor of DPP-4 enzyme. The ethanol extract of yacon leaves inhibits the DPP-4 enzyme with an IC50 of 856.9 ppm. The percentage inhibition of the DPP-4 enzyme by the enhydrin and uvedalin at a concentration of 250 ppm was 2.37 and 35.16%, respectively. The inhibitory potency of the pure isolated compounds was not substantially greater than that of the crude extract itself. This led us to the conclusion that the overall contribution of enhydrin and uvedalin to the extract's DPP-4 inhibitory activity is actually modest, suggesting the presence of other active compounds within the extract. However, it may provide a new approach to the treatment of type 2 diabetes.